Análisis de remoción de cadmio por acción de la microalga Chlorella sp. inmovilizada en perlas de alginato - Perenguez Ortega, Blanca Yomaira (2017)
Cadmium (Cd) is a metal that can interfere negatively in different metabolic routes of living beings, this project is objective was the evaluation al cadmium removal ability in aqueous solutions by means of Chlorella sp. in a concentration of 25x106 cells / mL immobilized on alginate pearls, and alginate beads without Chlorella sp. as witness. All treatments were established by triplicate, under constant aeration for 80 minutes, in aqueous solutions with four concentrations of cadmium at: 0 ppm, 20 ppm, 100 ppm and 200 ppm, taking samples of the liquid remnant every 10 minutes, to finally be read in the atomic absorption equipment with air-acetylene flame with cadmium lamp. The present study determined that Chlorella sp. immobilized removed 59,67% of cadmium metal at an initial concentration of 20 ppm leaving a 40,33% residue in the solution; Being the best removal result in a time of 80 min compared to the treatments at 100 ppm and 200 ppm of cadmium with presence and absence of the microalga.